Roles of property manager in effectiveness of maintenance management case study : D' Melor Condominium, Cyberjaya / Alya Batrisyia Mohd Rosli - Mohd Rosli, Alya Batrisyia (2010)
The purpose of this study is to measure the effectiveness of maintenance management of condominium at D'Melor Condominium, Cyberjaya. Unfit residents who live at condominium will give negative impact to the cleanness and building safety. The first objective is to study the work of the property manager in property maintenance and second objective is to identify the types or element done by the property manager in property maintenance. The third objective is to study the effectiveness of the property maintenance. Every types or element was divided into several more elements. Data were collected through interviews and questionnaire surveys. Respondent were taken by random from various block unit at condominium. Data analysis was carried out by applying descriptive analysis and frequency analysis. The findings show that the effectiveness of maintenance management in study area is effective while 22 elements or types from 25 elements or types from residents say that satisfactory by key elements or types measured. However, this building not achieve the highest effective status or highest satisfactory to respondent. The maintenance management could implement such as strengthen the maintenance part in organization structure and also upgrade a maintenance work system implementation which cover a planning and monitoring maintenance work.